The ratio of heart rate to heart rate variability reflects sympathetic activity during incremental cycling exercise. Issue 11 (2nd November 2022) - Tanoue, Yukiya; Komatsu, Tomohiro; Nakashima, Shihoko; Matsuda, Takuro; Michishita, Ryoma; Higaki, Yasuki; Uehara, Yoshinari
ABSTRACT: A low-frequency to a high-frequency component ratio (LF/HF) in heart rate variability (HRV) may not accurately reflect sympathetic nervous activity during exercise. Thus, a valid HRV-based index of sympathetic nervous activity is needed. Therefore, the heart rate to LF ratio (Heart rate/LF) was evaluated as sympathetic nervous activity index which is reflected by catecholamine levels during incremental exercise. In this study, 15 healthy adults performed an incremental exercise test using a cycle ergometer. HRV was derived from electrocardiography and HRV components related to the autonomic nervous system were obtained using frequency analysis. Heart rate/LF was calculated using the heart rate and LF component produced by HRV analysis. Catecholamine, blood lactate levels and respiratory gas were also measured throughout the exercise test. While LF/HF did not increase with increasing exercise intensity, Heart rate/LF non-linearly increased during the incremental exercise test, as did noradrenaline and blood lactate. Interestingly, Heart rate/LF values were positively correlated with noradrenaline ( ρ = 0.788, p < 0.05) and blood lactate ( ρ = 0.802, p < 0.05) levels and carbon dioxide production ( ρ = 0.903, p < 0.05) from at rest through the exercise stages. Heart rate/LF reflects sympathetic nervous activity and metabolic responses during incremental cycling exercise and has potential as an HRV index of sympathetic nervous activity during exercise. Trial registration: UMIN Japan identifier: UMIN000039639 .